Ubezpieczenia studenckie - Jakóbczak, Emilia; Nassalski, Tomasz; Ostrowska, Monika (Insurances for Students, 2007)
Project "Insurance for students" was created by The Actuarial Statistics Scientific Group in cooperation with The Survey Research Scientific Group. The main goal of this project is to compare insurance products for students that are available on the Polish market. There is a wide range of this kind of insurance: a student can buy a group insurance at his university or choose a very popular youth card that includes insurance. They can also buy an individual insurance. In this project, this group of insurances will not be compared because this product is expensive and students seldom choose it. The group insurance available at universities can be bought in dean's offices. Insurance companies are chosen by the authority of the university in cooperation with students' authority. The price of this kind of insurance is lower. Universities in Wroclaw offer different types of insurance. In this project, insurances offered at Wroclaw Agriculture University, Wroclaw University of Economics, Wroclaw University and Wroclaw University of Technology are compared. There are also student or youth cards that include insurance on the Polish market. They are very attractive because they offer additional benefits, like: discounts, travel assistance, helplines, press subscriptions, pre-booking of tickets to cultural events. The project includes the comparison of the cards: The Youth Planet, Euro <26, International Youth Travel Card (IYTC), Go 25, and International Student Identity Card (ISIC).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 123-135